EU budget reform: opportunities and challenges for global sustainable development - Christine Hackenesch; Julian Bergmann; Niels Keijzer; Svea Koch (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
With the next Multiannual Financial Framework (MFF), the EU will define not only the financial but also the political priorities until 2030. Which political objectives the EU intends to pursue in the future will therefore be a key issue during the MFF negotiations. The 2030 Agenda for Sustainable Development and its 17 Sustainable Develop¬ment Goals (SDGs), which the EU played a key role in shaping, should guide this debate. In terms of EU domestic policy, the 2030 Agenda should help the European budget be more strongly tuned towards socially disadvantaged groups, reduce the EU's environ¬mental footprint and promote sustainable economic growth. This, in turn, would enable the MFF to bolster public support for Europe. In terms of EU foreign relations, the 2030 Agenda requires the EU to not only focus on short-term security and migration policy interests but to allocate resources in the budget for supporting long-term sustainable development. This would allow the EU to position itself as a frontrunner for sustainable development – internationally as well as towards industrialised, emerging and developing countries. Two questions are central to the role of the 2030 Agenda in the next MFF: Where does the EU have the biggest deficits with respect to implementing the 2030 Agenda and the SDGs? And in which areas can the MFF make important contributions? We make five proposals on how to include the 2030 Agenda into the next MFF. These proposals complement one another and should be followed in parallel: (1) Embed the principles of the 2030 Agenda in the MFF: Individual principles of the 2030 Agenda, such as Leave no one behind, universality and policy coherence for sustainable devel¬op¬ment, call on the EU to take the SDGs into con¬sidera¬tion not only in its foreign but also domestic policies, for example in agricultural or structural funds. Moreover, these principles require the EU to reduce the negative impact of EU policies on third countries and to promote positive synergies. (2) Assign the SDGs to individual headings: The MFF should assign the global SDGs to individual headings and set minimum criteria for those SDGs and targets that each heading should contribute to. All headings should promote the three dimensions of sustainability – social, environ¬mental and economic. (3) Mainstream sustainability principle: The principle of sustainability should be mainstreamed across all headings, e.g. the current climate mainstreaming, should be supple¬mented by objectives for social and economic sustainability. (4) In heading IV (foreign relations), the EU should align its strategies for bilateral cooperation with the partners' SDG strategies. In addition, three to four thematic flagship programmes should be created for cooperation with countries of all income groups, such as in the areas of urbanisation, inequality or climate change. (5) Cross-cutting issues: The successor to the Horizon 2020 programme should invest more in research on sustainability. EU Impact Assessments should take greater account of the social and environmental dimensions of sustainability. The next MFF should set clear guidelines for sustainable procurement.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Agenda 2030